Finite Element Bus Rollover Test Verification - Abdul Hamid, I.; Kamarudin, K.A.; Osman, M.R.; Zainal Abidin, A.N.S.; Zulkipli, Z.H.; Mohd Jawi, Z.; Md Isa, M.H.; Solah, M.S.; Hamzah, A.; Ariffin, A.H. (Journal of the Society of Automotive Engineers Malaysia, 2021)
This study is conducted to verify the rollover test of the finite element bus model. Verification is a process of determining that a computational model accurately represents the theoretical mathematical model and its solutions. In case of bus rollover simulation, the verification process is by looking into its energy balance, in which all energy associated with the bus rollover process must be equal and preserved before and after the rollover. Any energy imbalance indicates errors in the rollover process and must be rectified so that the errors remain in acceptable tolerance. The main energies involved in calculations are potential energy, kinetic energy, internal energy, contact energy, rigidwall energy, damping energy, hourglass energy, and total energy. The finite element bus model used is CONTRAST bus developed by CM/E Group, Politecnico di Milano. The rollover test standard used is UN R66, and the software used to set up and solve the simulation are LS-PrePost and LS- DYNA. Energy balance and energy ratio from the rollover simulation shows that the verification procedure is followed, results are within acceptable values, and the rollover test is verified.